BANGKIT DARI KETERPURUKAN, PARENTING ANAK DENGAN GANGGUAN PENDENGARAN DAN TULI : LITERATURE REVIEW - Ganal Arief Rahmawan (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2019)
There are a lot of difficulties in taking care of children with hearing deficiency. Especially in parent-child communication. It is intriguing to know how parents’ response and measure after they find out that their children have hearing difficulty. The search of e-literatures was conducted to identify journals published within 10 years range concerning parenting to children with hearing problem. Electronic databases used were Proquest, Springer and Sage. The study conclude that parents feel stressed upon hearing that their children have learning difficulty. Mothers need an emotional support in order to keep themselves from neglecting the development of their children and also to stay strong in taking care of their children. They need professional help, talk therapy, hearing aid device, and counseling. Counseling is also important to parents in order to alleviate stress and professionals are capable of giving parents information they need in order to take care of their deaf children. Motivation from others, thinking positively, and being an optimists are keys to success of taking care children with hearing problems.